Proposal for a conceptual model for a SaaS ERP using an Open Source System - Natu, Raul Ashokchandra (2017)
Enterprise Resources Planning (ERP) systems are considered an important part in business organizations but with increasing global competition companies tend to seek more agile solutions that enable cost reduction at the same time. The paradigm change of Software as a Service (SaaS) came to revolutionize the delivery of applications at reduced costs, reliability and scalability. The ERP Open Source working in SaaS model will allow companies to extract all the benefits associated with the technologies used. This thesis presents a model and framework for ERP Open Source SaaS. The model and the framework are based on the literature review, and both were evaluated by empirical work. To validate the model and framework it was implemented an Open Source ERP which is already at market adapted to Portuguese reality. As a second validation of the artifact, the ERP was used for learning purposes by university students. Here are also reported the results of their use experience. This research shows that exist localized Open Source Software ERP alternatives that can be employed in a cloud context by companies.